1995
DOI: 10.1590/s0037-86821995000400009
|View full text |Cite
|
Sign up to set email alerts
|

Evolução temporal da resistência in vitro do Plasmodium falciparum às drogas antimaláricas em duas áreas da amazônia brasileira com distintas características sócio-econômicas e geográficas

Abstract: We evaluated the temporal progression of in vitro P. falciparum resistance to chloroquine, amodiaquine, quinine and mefloquine in two areas with distinct socioeconomical and geographical characteristics: Lourenço, in Amapá state and Paragominas, in Pará state. The former region is essentially an "open" gold mining camp, whereas the latter is one currently undergoing a colonization settlement process, in addition to expanding economical activities which mainly include cattle raising and wood exploitation. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The credibility of such programs depends on a high mefloquine efficacy. Although there seem to be no published reports of widespread mefloquine resistance in Brazil [5][6][7], periodic clinical trials should be conducted to monitor its efficacy, especially because of the possibility of mefloquine cross-resistance with quinine [8]. When we initiated this study, there had been no reported clinical studies of mefloquine in Brazil for over a decade, during which time mefloquine resistance rose dramatically in Southeast Asia [9].…”
mentioning
confidence: 99%
“…The credibility of such programs depends on a high mefloquine efficacy. Although there seem to be no published reports of widespread mefloquine resistance in Brazil [5][6][7], periodic clinical trials should be conducted to monitor its efficacy, especially because of the possibility of mefloquine cross-resistance with quinine [8]. When we initiated this study, there had been no reported clinical studies of mefloquine in Brazil for over a decade, during which time mefloquine resistance rose dramatically in Southeast Asia [9].…”
mentioning
confidence: 99%
“…As is known, self-medication and subcurative doses favor the selection of resistant parasite populations, which are frequent in areas of high malarial transmission. [8][9][10][11][12][13][14] Another factor that may influence the development of high resistance of P. falciparum to chloroquine (although no studies have been performed) could be the uncontrolled population migration movements within and into and out of the municipality of Domingo Sifontes and surrounding areas, as proposed above. Similar results have been showed by many authors.…”
Section: Resultsmentioning
confidence: 99%